Rats with Postinfarction Heart Failure: Effects of Propranolol Therapy on Intracellular Calcium Regulation and Left Ventricular Function - Sonwani, Hari Prasad (Journal of Cardiology and Cardiovascular Medicine, 2023)
Patients with heart failure may live longer if they receive chronic treatment with beta-adrenergic blocking medications. Unresolved are the mechanisms underlying the beneficial effects and if they may be applied to ischemic heart failure. Rats (n = 28) underwent echocardiographic-Doppler exams one and six weeks following a simulated operation or myocardial infarction (MI). After the first echocardiography, rats were randomized to either no therapy or 500 mg/l of propranolol in their drinking water. The noninfected left ventricular (LV) papillary muscles were used to record isometric contractions and intracellular Ca transients simultaneously. Untreated MI rats had a restrictive LV diastolic filling pattern, decreased systolic function (13% ± 2%), and significant LV dilatation (10.6 ± 0.4 mm vs. 8.9 ± 0.3 mm, MI vs. control). The LV chamber diameters of the propranolol-treated MI rats were 10.6 ± 0.5 mm, and systolic performance (13% ± 2%). Higher LV end-diastolic pressures (27 ± 2 mmHg vs. 20 ± 3 mmHg) and a more constrained LV diastolic filling pattern (increased ratio of early to late filling velocities and faster E wave deceleration rate) were seen in the propranolol-treated animals. Papillary muscle contractility in untreated MI rats was lower (1.6 ± 0.3 g mm²). Furthermore, the inotropic response to isoproterenol was attenuated, and Ca transients were extended. During isoproterenol stimulation, beta-adrenergic blocking administration had no effect on force development (1.6 ± 0.3 g mm²) or the length of Ca transients. Rats with postinfarction heart failure receiving chronic propranolol treatment did not have improvements in systolic function or LV remodeling. Propranolol exacerbated LV diastolic pressures and filling patterns. Additionally, there was no discernible improvement in intracellular contractility following treatment, Calcium control, or beta-adrenergic sensitivity in the myocardium that is not infarcted).